Clinical and laboratory characteristics of isolated lupus anticoagulants. Issue 165 (May 2018) - Mattia, E.; Tonello, M.; Del Ross, T.; Zerbinati, P.; Campello, E.; Simioni, P.; Ruffatti, A.
Highlights: Currently the clinical significance of isolated-LAC is controversial. Isolated LAC significantly prevailed in patients with disorders different from APS. The most sensitive test for detecting isolated LAC was the SCT assay. PTT-LAC had the highest specificity in detecting APS in patients with isolated LAC.